Bioactive PLGA–curcumin microparticle-embedded chitosan scaffold: in vitro and in vivo evaluation. (17th February 2017) - Amirthalingam, Muthukumar; Kasinathan, Narayanan; Amuthan, Arul; Mutalik, Srinivas; Sreenivasa Reddy, M.; Nayanabhirama, Udupa
Abstract: Wound healing is a complex process affected by several factors. In the present work, novel biocompatible PLGA–curcumin microparticle-embedded chitosan scaffold was fabricated for wound-healing application. Process variables involved in the preparation of microparticles were optimized using design of experiment. Scanning electron microscopy (SEM) confirmed the porous nature of scaffold with embedded microparticles. A maximum release of 14% of the encapsulated curcumin was observed at 12th hour. Modified tube dilution method showed that scaffold significantly ( p < 0.05) reduced multiplication of Staphylococcus aureus. More than 50% of the excised wound in rats healed in 4 days with an epithilization period of 18 days.